CHARACTERIZATION OF Citrillus colocynthis (MELON) SEED OIL AND ITS APPLICATION IN THE PRODUCTION OF COSMETICS - Omozuwa, O. P.; Ukhun, M. E.; Dibie, E. N.; Igbashio, Mercy D.; Anthony, P. C.; Osarobo, P. O. (FUDMA JOURNAL OF SCIENCES, 2024)
The study focused on the extraction, storage, and characterization of Citrillus colocynthis (melon) seed oil, as well as the production of perfume, soap, hair cream, and lip gloss using the extracted oil. The physicochemical characteristics of Citrillus colocynthis seed oil were investigated for a period of 0 to 2 months. We evaluated specific gravity, viscosity, volatile matter, appearance, and odor as physical parameters in the oil analysis and evaluated iodine value, saponification value, percentage free fatty acid (FFA), acid value, and peroxide value as chemical parameters. The results showed that the acid value was 1.04–1.05 mg KOH/g, the saponification value was 212.05–214.14 mg KOH/g, and the iodine value was 117.42–117.28 mg I2/100 g. It contained 0.45–0.58 mg KOH/g percent free fatty acid. The value of peroxide was 1.14–1.22 meq/kg. The appearance was golden-yellow and odorless. It had a volatile matter within the range of 0.06 and 0.07. The results also showed that the viscosity was between 39.01 and 39.88 mm2/s and the specific gravity was 0.90 and 0.85. The physiochemical characterization of the stored Citrillus colocynthis (melon) seed oil for a while conformed to Nigerian and international standards; hence, the plant seed oil may be edible and suitable for the formulation of various cosmetic products.
Keywords: Citrillus colocynthis; Seed oil; Production; Lip gloss; Perfume; Soap